The Arctiid Archetype: A New Lepidopteran Groundplan - Gawne, Richard; Nijhout, H. Frederik (Frontiers in Ecology and Evolution, 2020)
The nymphalid groundplan (NGP) has proven to be extraordinarily useful in the study of butterfly color patterns because it allows for the identification of homologous elements across species. It has long been thought that the NGP is broadly applicable to all Lepidoptera, implying that the characters which make-up butterfly color patterns are homologous to those found in the moths. However, this conjecture remains mostly untested. We analyzed the wing patterns of the hyper-diverse arctiid tiger moths, which are represented worldwide by approximately 11,000 species, and found that the color patterns of these animals can be parsed into a limited toolkit of homologous characters. Some of the pattern elements identified, such as the basal and central symmetry system, are present on the NGP, but their morphology is often quite different from what is seen in the butterflies. The border ocelli of the NGP appear to be absent altogether in the Arctiidae, and conversely, two distal pattern element we term the ‘van Bemmelen’ and ‘terminal’ bands are present in the color patterns of many arctiids, but are not represented on the NGP. In light of the observed differences, we derive a new theoretical groundplan based on the original NGP that we refer to as the ‘arctiid archetype.’ This model provides a comprehensive framework for understanding how the wing patterns of these animals develop, and yields novel insight into their evolutionary history.